Fourteen Years of Sustainability Reporting Research in Accounting: Bibliographic Studies - Rizky Yuniar SURURI; Y. Anni Aryani; Evi Gantyowati (Yayasan Ilomata, 2023)
Some companies that still apply the single-profit paradigm cause environmental damage, so there is a need for accountability to stakeholder through media sustainability reports. This study aimed to provide an overview of the development of sustainability reporting research for 14 years in Indonesia. Charting the field and analyzing community approach were used in this research. A research sample consisting of 50 articles obtained from 21 journals accredited Sinta 2 from 2009 to January 2022. The results indicated that the most widely used research method is the analytical method and the articles that received the most citations were published in 2015. In addition, this study also found that there are still research variables that are inconsistent with sustainability reporting, namely antecedent variables in the form of audit committees and consequence variables in the form of financial performance. Therefore, it is necessary to conduct an in-depth study to determine the cause of the inconsistency of these variables.